PENINGKATAN HASIL BELAJAR TEMATIK MELALUI TIPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISIONS) PADA SISWA KELAS V SDN CEMPAKA BARU 03 PAGI JAKARTA PUSAT - Siti Patonah; Ati Kusmawati (Khazanah Pendidikan, 2020)
ABSTRACT This study is entitled Improving Thematic Learning Outcomes Through Type STAD ( Student Teams Achievement Divisions ) in Class V Students of SDN Cempaka Baru 0 3 Pagi, Central Jakarta. Research conducted in the SDN Cempaka Baru 03 Pagi. This study uses a class action research type with the Kemmis and Mc Taggart models applied in two cycles. In the Pre-Cycle the researchers only used the type of lecture, the learning outcomes of students got an average grade for Indonesian Language content 56.16, and for Science content 61.81. In Cycle I, the researcher teaches students to use the STAD type and powerpoint media . In this Cycle I, student learning outcomes have increased with an average grade for Indonesian Language content 65.68, and for Science content 67.16. In the Cycle II the students can improve their abilities, more significantly by obtaining an average score of Indonesian Language content 80.23, and for Science content 81.48. With the success of learners who passed beyond KKM to charge Indonesian Language 80.65%, and 87.10% for the Science. By thus can be concluded that the learning of cooperative types STAD on the theme of Environment Our Best Friends can improve the outcomes of learning of students in class V SDN Cempaka Baru 03 Pagi. Keywords: Thematic Learning Outcomes , STAD Type .